MULTICULTURAL INSIGHTS CURRICULUM (Case Study of Islamic Religious Education Curriculum) - Oktrigana Wirian; Nelly Agustina (Proceeding International Seminar of Islamic Studies, 2022)
Diversity is an unavoidable destiny of God, and Indonesia is part of a nation that is rich in diversity. That is why multicultural issues are still relevant to be discussed. The most appropriate place to provide understanding and awareness about the importance of multiculturalism is through educational institutions. By using the literature study method, this paper will look closely at how to design an Islamic religious education curriculum with a multicultural perspective. The results of this study suggest that in order to internalize multicultural values in educational institutions, an Islamic religious education curriculum with a multicultural perspective is needed by making it a separate subject or inserting it into Islamic religious education subjects. Keywords: Curriculum, Study of Islamic Religious, multicultural